Protective Effect of the Vasopressin Agonist Terlipressin in a Rat Model of Contrast-Induced Nephropathy - VELİOĞLU, ARZU; AŞICIOĞLU, EBRU; ARIKAN, İZZET HAKKI; ÖZEN ALAHDAB, YEŞİM; YILMAZ, YUSUF; TUĞLULAR, ZÜBEYDE SERHAN (KARGER, 2011)
Background/Aims: Contrast-induced nephropathy (CIN) remains a leading cause of iatrogenic acute renal failure. Terlipressin, a long-acting analog of vasopressin, may improve renal function. This study aimed to investigate the possible protective effect of terlipressin against the development of experimental CIN in rats. Methods: Wistar albino rats (n = 32) were allocated randomly into four equal groups of 8 each, i.e. control, terlipressin, contrast media (CM), and terlipressin plus contrast media (TCM). CIN was induced by intravenous administration of indomethacin (10 mg/kg), N-nitro L-arginine methyl ester (L-NAME, 10 mg/kg, twice at 15 and 30 min), and high-osmolar contrast media meglumine amidotrizoate 60%. Renal function parameters, kidney histology, and tubular expression of vascular endothelial growth factor (VEGF) were determined. Results: Mean serum creatinine levels were decreased (p < 0.05) and creatinine clearance (p < 0.05) increased in the TCM group compared with the group. Notably, rats in the TCM group displayed less tubular necrosis (p < 0.05), medullary congestion (p < 0.05), and a reduced tubular expression of VEGF (p < 0.05) compared with the CM group. Conclusion: These results demonstrate that terlipressin can inhibit the development of CIN. Copyright (C) 2011 S. Karger AG, Basel
Keywords: Contrast-induced nephropathy; Terlipressin; Acute renal failure; ENDOTHELIAL GROWTH-FACTOR; HEPATORENAL-SYNDROME; KIDNEY INJURY; THERAPY; METAANALYSIS; PREVENTION; STRATEGIES; CIRRHOSIS; TRIALS